(untitled) (Majalah Kedokteran Bandung, 2021)
Supracondylar fractures of the humerus are common in children and the advocated treatments for these fractures include closed reduction and percutaneous pinning. There are numerous debates on the intervention period selection for delayed treatment in children. This phenomenon is prevalent in regions with limited healthcare support. The objective of this study was to compare the outcome of early and late treatment groups, including preliminary presentations and the management of failed treatment. This was a prospective comparative study on early and late open reduction, featuring Kirschner wire fixation for Gartland type III supracondylar fracture of humerus in children aged less than 18 years. Patients from January 2018 to January 2019 were categorized into early and late groups (n=22 and n=26), consisting of 33 (86.8%) males and 15 (31.25%) females. Flynn’s criteria were used to evaluate them. The average time from injury to surgery was 50.24±23.5 hours in the early group and 373.79±89.23 hours in the late group (p<0.002). While the Bauman’s angle recorded after 12 weeks presented the values of 82.04 ± 5.18 and 77.38±6.43 (p=0.622) for the early and late groups, respectively. Pre-operative nerve injuries were observed only in 4 (8.33%) cases from the early group. The functional outcomes of both categories were not significantly different statistically (p=0.242). The outcome for children with supracondylar humerus fracture Gartland type III was satisfactory in both groups. In conclusion, treatment delay does not result in a difference in the outcome according to Flynn’s criteria.